Acoustic waveguides: an attractive alternative for accurate and robust contact thermometry - Wang,Y; Zou,F; Cegla,F (Sensors and Actuators A: Physical, 2017)
We report a robust and very precise method of measuring temperature using ultrasonic waves. Solid stainless steel waveguides are used to provide well-defined and stable ultrasonic wave propagation paths. Ultrasonic wave velocity is strongly temperature dependent. The arrival times of the ultrasonic wavepackets along a waveguide are used to infer the average temperature of the waveguide. Our ultrasonic temperature measurements exhibit a high precision (i.e. ±0.015 C) that is more than two times better than the quoted accuracy of 1/10 DIN resistance temperature detectors (RTDs). The responsiveness of the waveguides was also investigated. While ultrasonic measurements can be made at very high frequencies, the responsiveness is limited by the heat transfer into the active sensing area. The waveguides make it easy to customise the dimension of the active sensing area and a shorter response time than those of RTDs has been demonstrated. The technique presented in this paper is a robust and cost effective alternative to other contact temperature measurements.